Silk Road Economic Belt: key risks and opportunities for Kazakhstan (Journal of Economic Research & Business Administration, 2022)
The article examines the Chinese project “Silk Road Economic Belt” (SREB) from the standpoint ofkey risks and benefits for Kazakhstan. In this aspect, a characteristic is given of the New Silk Road, thepossibility of using the republic’s potential for the implementation of the “One Belt, One Road” concept,the prospects for the development of cooperation between the PRC and the Eurasian EconomicUnion (EAEU). The relevance of the research topic is determined by the fact that Europe is intensivelyseeking access to Asian markets, and Asia is interested in the European market. The purpose, main directionsand ideas of scientific research is to establish the risks and opportunities for Kazakhstan in theimplementation of the Chinese SREB project. In the course of the study, it was found that for the CentralAsian countries, cooperation between the EAEU and the SREB seems to be a new era of developmentfor the entire Eurasian region. It can become a factor in economic growth, and for China – by improvingthe economic situation. Much attention is paid to the further development of transport potential and theformation of the logistics infrastructure of Kazakhstan, the development of oil and gas processing and theestablishment of the chemical industry.Key words: Great Silk Road, “One Belt, One Road”, Economic Belt of the Silk Road, transport andlogistics infrastructure, oil and gas processing, chemical industry.